Mr. Sjafruddin Prawiranegara : pemimpin bangsa dalam pusaran sejarah - Prawiranegara, Sjafruddin; Hakiem, Lukman; Noer, Mochammad, 1952- (Jakarta : Harian Republika, 2011)
Biography of Sjafruddin Prawiranegara, an Indonesian nationalist; volume commemorating of his centenary anniversary.
Includes bibliographical references.
Keywords: Prawiranegara, Sjafruddin; Nationalists -- Indonesia -- Biography; Indonesia -- History -- Revolution, 1945-1949.